PENGARUH KOMBINASI PUPUK ORGANIK CAIR DAN PADAT TERHADAP PERTUMBUHAN DAN PRODUKSI KACANG TANAH (Arachis hypogaea L.) - Imam Suntoro; Andri Prasetia; Jefri Sembiring (Musamus University, 2022)
ABSTRACT This study aims to determine the effect of the combination of liquid and solid organic fertilizer on the growth and production of peanuts (Arachis hypogaea L.). This research was carried out for four months, from January to June 2021, at the screen house of Musamus University, Merauke. The method used in this study was a Factorial Randomized Block Design (RBD) with two treatment factors, the first factor being liquid organic fertilizer and the second factor being solid organic fertilizer. The results showed that applying liquid organic fertilizer and solid organic fertilizer had no significant effect on all experimental parameters. However, using solid organic fertilizer with a dose of 200 g gave an average yield that tended to be better for the plant height parameter, which was 24,64 cm, and the number of branches reached 5,33 branches. The application of 300 ml of liquid organic fertilizer gave an average yield that tends to be better on the parameters of the number of pods, namely 24,33 pods dry pod weight 25,00 g, the number of pods contained 23,33 pods. In contrast, the two factors gave an average value in the combination treatment. The average tended to be suitable for the parameters of wet pod weight 34,67 g, and the number of empty pods 4,33 pods. In the highest treatment, the importance of dry pods when converted to hectares resulted in 6,25 tons/ha production. Keywords: peanut (Arachis hypogaea L.), liquid organic fertilizer, solid organic fertilizer, growth, and production